The use of folic acid, iron salts and other vitamins by pregnant women in the 2015 Pelotas birth cohort: is there socioeconomic inequality? - Vanessa Iribarrem Avena Miranda; Tatiane da Silva Dal Pizzol; Marysabel Pinto Telis Silveira; Sotero Serrate Mengue; Mariângela Freitas da Silveira; Bárbara Heather Lutz; Andréa Dâmaso Bertoldi (BMC, 2019)
Abstract Background Many low- and middle-income countries recommend micronutrient supplements for pregnant women to improve their nutritional status, prevent possible deficiencies and avoid fetal healgth consequences. This study evaluated the influence of socioeconomic status on the use of folic acid, iron salts and other vitamins and minerals among pregnant women in the 2015 Pelotas Birth Cohort. Methods This population-based birth cohort study was carried out with 4270 women. Participants were interviewed during pregnancy and at the maternity hospital about the antenatal period; including the use of iron salts, vitamins and other minerals. Descriptive analyses were performed to characterize the sample. The analyses were adjusted according to socioeconomic variables (maternal education, ethnicity, household income). Results The overall prevalence of the use of folic acid, iron salts or other vitamins and minerals was 91.0% (95% CI: 90.1-91.8). Specifically, 70.9% (95% CI: 69.5-72.3) used folic acid, 72.9% (95% CI: 71.5-74.3) used iron compounds, and 31.8% (95% CI: 30.3-33.2) used other vitamins or minerals. In the adjusted analysis, the use of iron salts was associated with nonwhite mothers, with ≤4 years of education and whose family income was less than or equal to the monthly minimum wage. The use of folic acid and other vitamins and minerals was associated with white mothers who were more highly educated and had a higher family income. Conclusion Although folic acid and other vitamins and minerals were more frequently used in white, richer and more educated mothers, which indicates inequality, iron supplements were more frequently used in the poorer, less educated nonwhite mothers, suggesting the opposite association for this supplement.